A Randomized, Double Blind, Placebo-Controlled Trial of Pioglitazone in Combination with Riluzole in Amyotrophic Lateral Sclerosis - Dupuis, Luc; Dengler, Reinhard; Heneka, Michael T.; Meyer, Thomas; Zierz, Stephan; Kassubek, Jan; Fischer, Wilhelm; Steiner, Franziska; Lindauer, Eva; Otto, Markus; Dreyhaupt, Jens; Grehl, Torsten; et al. (PLOS ONE, 2012)
Background Pioglitazone, an oral anti-diabetic that stimulates the PPAR-gamma transcription factor, increased survival of mice with amyotrophic lateral sclerosis (ALS). Methods/Principal Findings We performed a phase II, double blind, multicentre, placebo controlled trial of pioglitazone in ALS patients under riluzole. 219 patients were randomly assigned to receive 45 mg/day of pioglitazone or placebo (one: one allocation ratio). The primary endpoint was survival. Secondary endpoints included incidence of non-invasive ventilation and tracheotomy, and slopes of ALS-FRS, slow vital capacity, and quality of life as assessed using EUROQoL EQ-5D. The study was conducted under a two-stage group sequential test, allowing to stop for futility or superiority after interim analysis. Shortly after interim analysis, 30 patients under pioglitazone and 24 patients under placebo had died. The trial was stopped for futility; the hazard ratio for primary endpoint was 1.21 (95% CI: 0.71–2.07, p = 0.48). Secondary endpoints were not modified by pioglitazone treatment. Pioglitazone was well tolerated. Conclusion/Significance Pioglitazone has no beneficial effects on the survival of ALS patients as add-on therapy to riluzole. Trial Registration Clinicaltrials.gov NCT00690118.